The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1600-0668.2004.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of single and mixed VOCs by smell and by sensory irritation

Abstract: We have measured complete concentration-detection (i.e., psychometric or detectability) functions to study the olfactory and ocular/nasal chemesthetic (a term that includes sensory irritation ) impact of VOCs presented singly and in various binary mixtures. Such functions provide considerably more information than that provided by measuring only a "threshold". The outcome for single VOCs confirmed the much higher absolute sensitivity of olfaction compared to chemesthesis, but also demonstrated that the detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 37 publications
0
42
0
2
Order By: Relevance
“…Notably, experiments within the same study (Oka Y et al, 2006) have shown that whereas delivery of the odorant as a vapor still needs to reach μM concentrations when the response is measured at the cell level (e.g., HEK293 or isolated olfactory sensory neurons: OSNs), it only needs to reach nM concentrations when the response is measured at the glomerular level. Thus, responses measured beyond the individual cell level, be it at the olfactory bulb (mouse) (Oka Y et al, 2006), the antennal lobe (fly) (Pelz D et al, 2006), or the integrated olfactory system (human) (this study; Cain WS et al, 2007b;Cometto-Muñiz JE et al, 2004;Wise PM et al, 2007), produce EC 50 s at or below the nM range. In terms of concentration span, the odorant response often rises from background to maximum within approximately two log units of concentration but this span can vary from one {e.g., (Kajiya K et al, 2001)} to three {e.g., (Abaffy T et al, 2006)} log units, irrespective of stimulus phase (liquid or vapor) or level at which the olfactory path is probed.…”
Section: Vapor Concentration Range Issuesmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, experiments within the same study (Oka Y et al, 2006) have shown that whereas delivery of the odorant as a vapor still needs to reach μM concentrations when the response is measured at the cell level (e.g., HEK293 or isolated olfactory sensory neurons: OSNs), it only needs to reach nM concentrations when the response is measured at the glomerular level. Thus, responses measured beyond the individual cell level, be it at the olfactory bulb (mouse) (Oka Y et al, 2006), the antennal lobe (fly) (Pelz D et al, 2006), or the integrated olfactory system (human) (this study; Cain WS et al, 2007b;Cometto-Muñiz JE et al, 2004;Wise PM et al, 2007), produce EC 50 s at or below the nM range. In terms of concentration span, the odorant response often rises from background to maximum within approximately two log units of concentration but this span can vary from one {e.g., (Kajiya K et al, 2001)} to three {e.g., (Abaffy T et al, 2006)} log units, irrespective of stimulus phase (liquid or vapor) or level at which the olfactory path is probed.…”
Section: Vapor Concentration Range Issuesmentioning
confidence: 96%
“…Few have gone further and measured concentration-detection functions Cain WS, Gent JF, 1991;Cain WS et al, 2007a;Cometto-Muñiz JE et al, 2002). Even fewer have measured these functions for a number of odorants in the context of addressing structure-activity, e.g., (Cometto-Muñiz JE et al, 2004;Wise PM et al, 2007). Our own previous work has included measuring odor thresholds along and across homologous series, using a uniform procedure , with the goal of studying enough odorants to propose a structureactivity model for the short-term (1-3 sec) odor detection of volatile organic compounds (VOCs) by humans Abraham MH et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We start with the psychometric plots obtained from the probability of sensory irritation detection, Q, of a given VOC as a function of its gaseous concentration, log P with P in ppm (Cometto-Muñiz et al, 1999;2001a;2002;2004a;2004b;2007b;2008;Cain et al, 2006). As for the determination of thresholds, this involves a panel of human subjects.…”
Section: The Psychometric Plotsmentioning
confidence: 99%
“…For sensory irritation, the plot is extraordinarily steep, and the difference in log P corresponding to chance detection, Q = 0, and perfect detection, Q = 1, is typically around one log unit, e.g. (Cometto-Muñiz et al, 2002;2004b). This is indicated on the plot by Δ, where 2Δ = one log unit in log P. The log P value corresponding to Q = 0.5, is that of the detection threshold, shown as log P 0.5 .…”
Section: The Psychometric Plotsmentioning
confidence: 99%
See 1 more Smart Citation